Epidemiology and management of primary immune thrombocytopenia: A nationwide population-based study in Korea. Issue 155 (July 2017) - Lee, Ji Yun; Lee, Ju-Hyun; Lee, Heeyoung; Kang, Beodeul; Kim, Ji-Won; Kim, Se Hyun; Lee, Jeong-Ok; Kim, Jin Won; Kim, Yu Jung; Lee, Keun-Wook; Kim, Jee Hyun; Choi, Hyoung Soo; et al.
Abstract: Introduction: The epidemiology of immune thrombocytopenia (ITP) is not well characterized in an Asian population. Materials and methods: From July 2010 to June 2014, ITP patients were identified using the Korean Health Insurance Review and Assessment Service database. Results: The overall incidence rate of ITP was 5.3 per 100, 000 person-years (95% CI: 5.1–5.5). The overall incidence rate ratios of children under 15 years old to adults and females to males were 3.8 (95% CI: 3.7–3.9) and 1.3 (95% CI: 1.2–1.4), respectively. Of the total 10, 814 patients, 3388 patients (31%) needed treatment for ITP; of these, 54% continued treatment for more than three months. First-line therapy consisted of corticosteroids (CS) in 42%, immunoglobulin (IVIg) in 35%, CS with IVIg in 19%, and other immunosuppressive agents (ISA) in 4%. Among treated patients, 75% of adults and 33% of children continued treatment for more than three months. After three months, the most frequently used drug was CS alone in 63% of patients. Only 104 patients underwent splenectomy; of these, 51% received salvage treatment after a median of one month after surgery (range: 0–27). The proportion of patients who received platelet transfusions of 12 units or more per month for at least two consecutive months was significantly higher among patients treated for more than three months compared with patients who completed treatment within three months. Conclusions: This population-based study is the first to describe the incidence of ITP and its treatment reality for patients in Korea. Highlights: The epidemiology of ITP in Asian population is unknown. We evaluated the nationwide incidence and practice patterns of ITP. The incidence of immune thrombocytopenia was 5.3 per 100, 000 person-years in Korea. Of the treated patients for ITP, 53% continued treatment for more than three months.